Potentialities of line planting technique in rehabilitation of logged over area referred to species diversity, growth and soil quality - PRIJANTO PAMOENGKAS (Biodiversitas Journal of Biological Diversity, 2010)
Pamoengkas P (2010) Potentialities of line planting technique in rehabilitation of logged over area referred to species diversity, growth and soil quality. Biodiversitas 11: 34-39. Human interventions in the utilization of tropical forest resources are experiencing unanticipated consequences. The selective logging practices generally cause considerable damage to vegetation and the soil surface. It is supposed that soil condition and vegetation growth rate is deteriorated and reduced. Therefore, scientist strongly argue that the only wayto achieve sustainability of Indonesian natural forest will require that the production natural forest is managed through methods that are acceptable from the perspective of environment as well as timber production. This means that there will be a strong need and incentive for methods and innovative technology. For more than two decades, tropical rainforest in Indonesia have been managed intensively under the Indonesian selective cutting (TPI) and later on by the Indonesian selective cutting and replanting (TPTI) and then, selective cutting and line planting (TPTJ) system. TPTJ, as one example of selective cutting, recently become a proper alternative should be takeninto consideration in the management of production natural forest in Indonesia by planting dipterocarp species in line. In this system, planting line (width 3 m) and intermediate line (width 17 m) are made alternately. The initial width of line is 3 m and to be expanded until 10 m within 5 years to introduce more light. The objective of this research was to assess growth and soil quality of TPTJ system. The object of research was TPTJ plot of various ages from 1 year to 7 years. For achieving the objective, 14 sample plots measuring 200 m x 200 m each, were laid out at research plots. The result showed that growth respond of Shorea leprosula toward the width of planting line was better comparing to Shorea parvifolia, but generally from this growth assessment it seems that individual tree has a successfully performance. In terms of soil quality, it was seen that planting line establishment of 3 m and more, does not cause soil properties decrease in the whole plots.Key words: selective logging, production forest, selective cutting and line planting, dipterocarp species, growth, soil quality.